Analysis and Zonation of Land Vulnerability Areas in Pekon Karangrejo Ulubelu Tanggamus Using Microzonation Method - Eko Rananda; Lintang Prabowo; Arief Putih Prabowo; Syamsurijal Rasimeng; Ida Bagus Suananda Yogi (Himpunan Ahli Geofisika Indonesia (HAGI), 2020)
Abstract.Ulubelu Tanggamus is an area that have geothermal energy potential. This region consists of a geological structure in the form of graben and reverse fault formed between Mount Rendingan and Mount Kukusan. Identifications that can be done include surveys to map soil characteristics in shaking responses using microzonation methods. This study aims to analyze the values ​​of dominant frequency, dominant period, Vs30 and amplification. The stages of the research carried out are processing data to obtain dominant frequency, calculating the value of the dominant period, calculating the value of Vs30 and the amplification value, and making a map of the soil vulnerability of the UlubeluTanggamus area. Based on the distribution of the dominant frequency values, the UlubeluTanggamus geothermal area is dominated by a dominant Frequency (F0) >0.5Hz which is expected to be a very thick surface thickness of sediments more than 30m. The distribution of the dominant period value obtained is (T0)>1 where the character of the sedimentary rock type is very soft consisting of alluvial material formed from sedimentation of deltas, top soil, and mud. The distribution of the Vs30 value is dominated by the value of 100 <Vs30<200 and obtains an amplification value of 2<A0<6 times where the area is an area with a moderate risk category to the danger of soil vulnerability.